Tale er sølv: Om begrebet syntaktisk ellipse - Brink, Lars; Schack, Jørgen (Danske Studier, 2024)
The purpose of this paper is to contribute to the theoretical discussion and definition of the concept of syntactic ellipsis. The main focus is on constructions that may serve to illustrate what, in our view, should be and what should not be considered elliptic. The description of ellipsis in current linguistic literature is fairly uniform. According to most definitions, an »incomplete« construction must fulfil the »condition of recoverability« in order to be considered elliptic, i.e. the »missing« elements should be semantically recoverable from the context. Consequently, the elliptic construction and the recovered full form must have the same meaning. This condition, however, is not always satisfied by constructions presented as elliptic in current grammars. According to our definition of ellipsis, synonymy is crucial, but we propose another even more basic condition, namely the »condition of construal«: in order to be considered elliptic, a construction must be construed as a shortening of another construction. If native speakers in general do not construe an utterance as a shortening of a fuller form, there is nothing to recover. Hence, the utterance is not an ellipsis.